1987
DOI: 10.1042/bj2470151
|View full text |Cite
|
Sign up to set email alerts
|

Acute alterations in sodium flux in vitro lead to decreased myofibrillar protein breakdown in rat skeletal muscle

Abstract: Myofibrillar protein breakdown was evaluated by measuring the release of N tau-methylhistidine by isolated rat skeletal muscles or perfused rat muscles in the presence of a variety of agents known to affect Na+ flux. Total cell proteolysis was evaluated simultaneously by measuring tyrosine release by muscles after the inhibition of protein synthesis with cycloheximide. Treatment of muscles with the Na+ ionophore monensin or inhibitors of Na+-K+ ATPase (ouabain, digoxin or vanadate) decreased N tau-methylhistid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…For example, TPA inhibits 3-MH release from EDL muscle in vitro (Goodman, 1987) and from C 2 C 12 myotubes (Thompson et al, 1996). This suggests that the PKC family may play an important role in the regulation of myofibrillar protein degradation (Thompson and Palmer, 1998) and that specific isoforms might represent important targets for intervention therapies in various disease states (Palmer and Thompson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TPA inhibits 3-MH release from EDL muscle in vitro (Goodman, 1987) and from C 2 C 12 myotubes (Thompson et al, 1996). This suggests that the PKC family may play an important role in the regulation of myofibrillar protein degradation (Thompson and Palmer, 1998) and that specific isoforms might represent important targets for intervention therapies in various disease states (Palmer and Thompson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that current methodology (high performance liquid chromatography) is able to measure 3-MH release in these quantities when muscle is incubated in the absence of any other amino acids (e.g., Goodman, 1987). However, such conditions may lead to abnormally high degradation rates and we have found that when physiological concentrations of amino acids are present, detection of these levels of 3-MH is not possible.…”
Section: Discussionmentioning
confidence: 70%
“…To overcome these problems, intact muscle incubated 0 1996 WILEY-LISS, INC. in vitro has been used (e.g., Goodman, 1987). However, to investigate the signalling pathway(s1 which regulate 3-MH release in such a model still poses considerable problems of interpretation.…”
mentioning
confidence: 99%
“…Previous studies in this (4 -6) and other (7) laboratories have shown that these two agents both stimulate protein synthesis and reduce the release of N -methylhistidine, a marker of myofibrillar protein degradation from intact skeletal muscle in vitro and skeletal muscle cells in culture. However, the mechanism(s) mediating these effects are poorly understood.…”
mentioning
confidence: 83%
“…Although PLD is clearly not involved in the stimulation of protein synthesis by vasopressin, both this agonist and TPA also reduce myofibrillar protein degradation in skeletal muscle (6,7). It remains to be determined whether PLD plays a role in the regulation of this component of protein turnover.…”
Section: Stimulation Of Protein Synthesis By Exogenous Pld-mentioning
confidence: 99%